IMPLEMENTASI SISTEM ABSENSI SISWA BERBASIS QRCODE MENGGUNAKAN ANDROID STUDY KASUS SMKN 8 BANDAR LAMPUNG - zainal farizi (Universitas Teknokrat Indonesia, 2023)
Implementation of a QR Code-Based Student Attendance System Using Android Case Study SMKN 8 Bandar Lampung is a thesis that aims to develop a QR Code-based student attendance system using the Android platform at SMKN 8 Bandar Lampung. The development method used is the waterfall method, which consists of the stages of analysis, design, implementation, testing and maintenance. This research also covers the limitations of the problems and benefits of using a QR Code based attendance system. In conclusion, the implementation of a QR Code-based attendance system using Android at SMKN 8 Bandar Lampung can increase the efficiency of the student attendance process and get positive responses from students and teachers. This system also has benefits in terms of saving time and costs and minimizing human errors in the attendance process. However, this research has limitations on the implementation of student attendance systems only and does not discuss the implementation of attendance systems in other schools.